2017
DOI: 10.1039/c6rp00233a
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes, self-efficacy and experiences in a modified process-oriented guided inquiry learning undergraduate chemistry classroom

Abstract: This one-semester, mixed methods study underpinning social cognition and theory of planned behaviour investigated the attitudes, self-efficacy, and experiences of 559 first year undergraduate chemistry students from two cohorts in modified process-oriented guided inquiry learning (POGIL) classes. Versions of attitude toward the study of chemistry (ASCI v2), and chemistry attitudes and experiences questionnaire (CAEQ) were adopted, modified, and administered to understand and gauge students’ affective outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 60 publications
6
60
0
10
Order By: Relevance
“…Cohen's d values were also computed to estimate the effect sizes between the groups. The effect size values were later examined in accordance with the acceptable (Vishnumolakala, Southam, Treagust, Mocerino and Quresh, ; Creswell, ) range: small effect (0.2–0.30), medium effect (0.40–0.70) and larger effect (0.8 and above). The results are presented in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…Cohen's d values were also computed to estimate the effect sizes between the groups. The effect size values were later examined in accordance with the acceptable (Vishnumolakala, Southam, Treagust, Mocerino and Quresh, ; Creswell, ) range: small effect (0.2–0.30), medium effect (0.40–0.70) and larger effect (0.8 and above). The results are presented in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…Guided inquiry is one of the various inquiry learning models which mainly consists of five steps, namely observation, manipulation, generalization, verification and application (Vishnumolakala, Southam, Treagust, Mocerino, & Qureshi, 2017;Fay, Grove, Towns, & Bretz, 2007;MartinHansen, 2002). Guided inquiry provides guidance in formulating investigative questions and/or other phases if required commonly for learners whose inquiry skill has not committed or established (Banchi, H., Bell, 2008;Wenning & Khan, 2011;Shen, 2007;Kuhlthau, 2010;Dounas-Frazer & Reinholz, 2015;Vishnumolakala et al, 2017). Learning performances such as observing of investigation pursuing phenomena, formulating investigative questions, and designing investigative experiments are…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most students in this population are in their second year of the undergraduate studies when involvement in research activities are encouraged, providing an outlet to increase self‐efficacy, along with it the likelihood of both male and female students' degree completion and career choices within science (Betz & Hackett, ; Zeldin, Britner, & Pajares, ). The use of process‐oriented guided inquiry learning (POGIL; Qureshi, Vishnumolakala, Southam, & Treagust, ; Vishnumolakala, Southam, Treagust, Mocerino, & Qureshi, ), problem‐based learning (Mataka & Kowalske, ), and collaborative learning (Fencl & Scheel, ) are associated with increased self‐efficacy. Conversely, one study found no impact of POGIL on self‐efficacy (Chase, Pakhira, & Stains, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our research supports those results, and indicates that measuring self-concept, specifically, can help an instructor identify at-risk students before the first term assessment. The recognized influence of score on the first examination on all subsequent measures of achievement (Villafañe et al, 2016) suggests that an initial measure of self-concept can inform an instructor as to which students may be at risk of performing poorly in the class as a whole, at which point they may decide to incorporate interventions which may improve affective and academic measures (Espinosa, 2008(Espinosa, , 2011Mataka & Kowalske, 2015;Ong, Wright, Espinosa, & Orfield, 2011;Qureshi et al, 2017;Vishnumolakala et al, 2017).…”
Section: Implications For Instructionmentioning
confidence: 99%